Recovering Identity from Anorexia Nervosa: Women's Constructions of Their Experiences of Recovery from Anorexia Nervosa Over 10 Years. Issue 1 (2nd January 2018) - Conti, Janet E.
Abstract : There is little consensus about the meaning of recovery in anorexia nervosa with most studies focusing on researcher selected variables of weight gain and improvement in eating disorder symptomatology. There is also a paucity of research that focuses on how the experiencing person themselves define recovery and whether this term is useful to them to depict their journey of reclaiming their life and identity from anorexia nervosa. This article explores 21 Australian women's experiences of anorexia nervosa (AN) over 10 years and the ways they negotiated their identities in relation to the question of recovery. The research interviews sought to provide a context for these women to speak on their own terms, terms not confined to the medical discourse. The discursively constructed category of recovery was troublesome for the majority of these women, despite the researcher inadvertently taking up this category in lines of questioning, particularly in the earlier interviews. Most troubling for the women was the assumption that recovery erased their experiences with the expectation that they should return to a pre-illness state. On the other hand, speaking on their own terms—including the use of metaphor and (re)authoring their experiences as an identity journey—was significant in scaffolding the women toward narratives of reclaiming their lives and identities from AN and its effects. The women in this study refused to confine the terms of their speaking to a recovery discourse; instead, they honored the narratives of their experiences and histories as profound in their identity formation. The implications of this research are significant given that the majority of research and many treatments to date confine the terms of speaking to the "anorexia" discourse.